Predicted distributions of avian specialists: A framework for conservation of endangered forests under future climates. Issue 6 (15th March 2020) - Colyn, Robin B.; Ehlers Smith, David A.; Ehlers Smith, Yvette C.; Smit‐Robinson, Hanneline; Downs, Colleen T.
Abstract: Aim: Forested regions are of global importance for a multitude of ecosystem functions and services and are critical for biodiversity. Anthropogenic climate‐change compounds negative effects of land‐use change on forest persistence and forest‐dependent biodiversity. Habitat loss and climate change have an additive effect and drive species' extinctions in similar ways, resulting in a homogenization of biodiversity. Connectivity is key in conservation planning for mitigating climate change effects and facilitating species' abilities to disperse throughout remnant habitat and track their climate niches. We used three forest‐specialized and habitat‐specific bird species as focal species to understand avian connectivity and conservation of each of South Africa's three threatened forest classes, as each species is range‐restricted to its respective forest type. Location: South Africa. Methods: We created ensemble models of species' distributions and combined core home‐ and breeding‐range patches with a hybrid of least‐cost pathways and ecological circuit theory linkages to assess the success of corridors in facilitating connectivity of each of the three forest types. We then predicted the likelihood of niche persistence for each species under future climate‐change scenarios, and the efficacy of our connectivity modelling to facilitate range expansion or climate‐niche tracking. Results: The projected habitat loss under climate‐change scenarios impacted core‐habitat patch distribution, size and connectivity, exacerbated habitat fragmentation and increased resistance and the severity of pinch points and barriers along dispersal corridors. Forest systems and associated focal species projected to experience the highest levels of habitat loss/contraction occurred at mid‐ to high elevations. Climate‐change resilience across ecosystems, and persistence of species therein, was dependent on connectivity, facilitating species' ability to track specific climate niches. Main conclusions: Climate‐change resilience of ecosystems, and persistence of biodiversity therein, is most likely to be a product of high functional biodiversity, connectedness and the ability of species to track specific climate niches.